A novel Melnikomyces species from forest litter in China - Wei, Tian-Peng; Zhang, Xin; Ren, Peng-Peng; Jiang, Yu-Lan (Phytotaxa, 2020)
A new species, Melnikomyces longisporum sp. nov. was isolated from forest litter in Guizhou Province, China. Phylogenetic analysis based on a combined nuclear ribosomal markers (SSU, ITS, and LSU) and protein coding genes (ACT1, TUB2, and TEF1-α) sequence data indicated that this strain belonged to the genus Melnikomyces but it constituted a distinct lineage and represented herein as a novel taxon. Morphological examination showed that it can be distinguished from known Melnikomyces species by its longer branched conidiophores, and longer verruculose conidia.